2013
DOI: 10.3390/publications2010001
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Doctors Connecting to the English Publishing World: Literature Access, Editorial Services, and Training in Publication Skills

Abstract: In the literature on academic publishing, little attention has been paid to the needs and concerns of non-English-speaking researchers in professional contexts. This paper addresses the gap in that literature by providing insights into the situation with medical doctors in China. Following an overview of the broad picture, I will report a case study, which was conducted at a major hospital in East China and which aimed at exploring how a group of orthopedic surgeons access the English medical literature and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…We have previously proposed that wrongly identified nucleotide sequences in the context of repetitive and superficially justified gene research could reflect the external involvement of organisations such as paper mills ( 8 , 13 , 24 , 26 ). Although researchers in different countries may use paper mills to meet publication targets or quotas ( 47 ), paper mills have been most widely discussed in the context of academics and medical doctors in China ( 25 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ). Stringent publication requirements may represent a particular challenge for hospital doctors in China, where some hospital doctors have described limited time, training and/or opportunities to undertake research ( 25 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously proposed that wrongly identified nucleotide sequences in the context of repetitive and superficially justified gene research could reflect the external involvement of organisations such as paper mills ( 8 , 13 , 24 , 26 ). Although researchers in different countries may use paper mills to meet publication targets or quotas ( 47 ), paper mills have been most widely discussed in the context of academics and medical doctors in China ( 25 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ). Stringent publication requirements may represent a particular challenge for hospital doctors in China, where some hospital doctors have described limited time, training and/or opportunities to undertake research ( 25 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although researchers in different countries may use paper mills to meet publication targets or quotas ( 47 ), paper mills have been most widely discussed in the context of academics and medical doctors in China ( 25 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ). Stringent publication requirements may represent a particular challenge for hospital doctors in China, where some hospital doctors have described limited time, training and/or opportunities to undertake research ( 25 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ). While recognising that articles with wrongly identified sequences from hospitals in China may reflect broader literature trends ( 25 , 56 ), the large numbers of human gene research articles with incorrect nucleotide sequences that list hospital affiliations in China could reflect hospital doctors turning to paper mills to meet publication requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lillis and Curry (2010), investigating non-Anglophone European academics in education and psychology, conclude that colleagues are the most valuable publishing resource for EAL scholars, a finding echoed by Li (2014b) studying a group of surgeons at a Chinese hospital. Research on Iranian medical scholars, on the other hand, found that colleagues lacked the confidence and literacy skills to rectify their fellow researchers' papers (Gholami and Zeinolabedini 2017;Zeinolabedini and Gholami 2016).…”
Section: Collegial Support For Eal Academicsmentioning
confidence: 99%
“…Other personal relations, or family relations to be more specific, have facilitated my access to researchers beyond academia, i.e., doctors and medical students at a Chinese hospital engaging in research for publication (e.g., [34,35]). Evidence can be gleaned from the literature to indicate that family relations can sometimes be an important factor in shaping one's research path.…”
Section: Accessing Participants Through Personal Contactsmentioning
confidence: 99%